2013
DOI: 10.1080/09500693.2013.867089
|View full text |Cite
|
Sign up to set email alerts
|

Students' Visualization of Metallic Bonding and the Malleability of Metals

Abstract: This study investigated the mental representations of metallic bonding and the malleability of metals held by three male students aged 14-15 (Year 10) who were attending a Hong Kong school. One student was selected by their chemistry teacher as representing each of the highest, the medium, and the lowest level of attainment in chemistry in a school that admitted students of average general attainment. The students were interviewed and their understandings probed through their provision of drawings and their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
2
26
0
1
Order By: Relevance
“…Furthermore, the use of different representational modes, both by the students and the teacher, supported communication in the classroom, allowing for mutual understanding and the negotiation of meanings. This result was seen to be in line with other studies that highlight the fact that different resources for communication are common and necessary in science, especially in the case of chemistry (Adadan, 2013;Cheng & Gilbert, 2014;Gilbert, 2005;Kozma & Russell, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the use of different representational modes, both by the students and the teacher, supported communication in the classroom, allowing for mutual understanding and the negotiation of meanings. This result was seen to be in line with other studies that highlight the fact that different resources for communication are common and necessary in science, especially in the case of chemistry (Adadan, 2013;Cheng & Gilbert, 2014;Gilbert, 2005;Kozma & Russell, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have suggested that students face many challenges in learning this model (de Posada, 1997;Taber, 2003b;Coll & Treagust, 2003). In an interview study, Cheng and Gilbert (2014) postulated that the learning was challenging because it involved a conceptual change from the focus on structure (in the simple particle model) to a focus on the intangible electrostatic force also (in the free electron model). We sought to extend their work by examining a larger population of students to determine whether learning the electrostatic force was more challenging than learning it as a structure.…”
Section: Two Models Of Metals In School Chemistrymentioning
confidence: 99%
“…The learning of the free electron model of metallic bonding based on the existing knowledge of the simple particle model arguably involves an ontological shift. It has been shown that such a shift might present a big challenge to students (Cheng & Gilbert, 2014).…”
Section: Conceptual Change In Learning the Free Electron Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of using visual cues in combination with verbal cues during chemistry instruction and problem solving has been pointed out in previous research (Cheng & Gilbert, 2014;Sanger & Greenbowe, 2000). Whereas words are coded verbally, students are more likely to code diagrams both verbally and visually.…”
Section: Dual Coding Theory Of Information Processingmentioning
confidence: 91%